Pengaruh ROE dan Pertumbuhan Penjualan terhadap Harga Saham Perusahaan - Meindro Waskito (AKRUAL : Jurnal Akuntansi dan Keuangan, 2021)
This study aims to determine the effect of Return on Equity (ROE) and Sales Growth on Company Stock Prices. The sample used in the study was a company listed on the Indonesia Stock Exchange, namely Automotive and Component companies and published financial reports in 2015-2019 with 8 samples using purposive sampling. The independent variables of this study are Return on Equity and Sales Growth. The dependent variable is the stock price. The results partially show that Return on Equity (X1) has a significant negative effect on stock prices (Y). Meanwhile, Sales Growth (X2) has no significant positive effect on Stock Prices (Y). In this study, the adjusted R2 value obtained from the Random Effects model is 0.126571, this shows that the contribution of the independent variables, namely Return on Equity and Sales Growth, can affect the dependent variable, namely the Stock Price of 12.66% at the 5% level of significance. while the rest of 87.34% is influenced by other variables outside the research.